EVALUATION OF THE IMPLEMENTATION OF THE HACCP SYSTEM AND ITS EFFECTS ON EFFICIENCY AND WASTE REDUCTION - Defrein, Talita; Geiza dos Anjos, Andréa; Zimmermann, Guilherme (Revista Gênero e Interdisciplinaridade, 2025)
The responsibility of food industries in ensuring the quality and safety of their products is essential, especially in response to increasing consumer demands and regulatory requirements. To meet these expectations, quality management tools must be effectively implemented. While Good Manufacturing Practices (GMP) are mandatory and fundamental prerequisites, the Hazard Analysis and Critical Control Points (HACCP) system provides a structured approach for guaranteeing and managing food safety. This study presents the methodology used for implementing HACCP in a minimally processed vegetable industry, specifically focusing on the lettuce production chain. The objective was to evaluate the effectiveness of the HACCP system implementation. Procedures and HACCP plan forms were developed to control and minimize Critical Control Points (CCPs) based on the system’s seven principles. Results demonstrated a reduction in customer complaints and positive outcomes in microbiological analyses conducted during and after implementation. These findings indicate the production of safer, higher-quality foods, with lower costs and greater consumer acceptance. Although applied to only one production line—lettuce—the positive results support expanding HACCP to other processes and products within the industry, strengthening implementation and team engagement. Additionally, the study highlights how HACCP contributes to reducing food waste by minimizing failures, rework, and losses throughout the production chain, aligning with SDG 12: Responsible Consumption and Production.